Developmental Atrazine Exposure Suppresses Immune Function in Male, but not Female Sprague-Dawley Rats - Andrew A. Rooney (2003)
Each year, 75 million pounds of the broadleaf herbicide atrazine (ATR) are applied to crops in the United States. Despite limited solubility, ATR is common in ground and surface water, making it of regulatory concern. ATR suppresses the immunomodulatory hormones prolactin (PRL) and the thyroid hormones (THs), with developmental exposure to ATR permanently disrupting PRL regulation. We hypothesized that ATR may cause developmental immunotoxicity through its disruption of PRL or THs. To test this hypothesis, pregnant Sprague-Dawley (SD) rats were exposed to 35-mg ATR/kg/d from gestational day (GD) 10 through postnatal day (PND) 23. Separate groups were exposed to bromocryptine (BCR) at 0.2 mg/kg/2x/day to induce hypoprolactinemia or to propylthiouracil (PTU) at 2 mg/kg/day to induce hypothyroidism. After the offspring reached immunologic maturity (at least 7 weeks old), the following immune functions were evaluated: natural killer (NK) cell function; delayed-type hypersensitivity (DTH) responses; phagocytic activity of peritoneal macrophages; and antibody response to sheep erythrocytes (SRBC). ATR decreased the primary antibody and DTH responses in male offspring only. Neither PTU nor BCR caused immunosuppression in any measured variable, although PTU increased phagocytosis by peritoneal macrophages. These results demonstrate that developmental exposure to ATR produced gender-specific changes in immune function in adult rats and suggest that immune changes associated with ATR are not mediated through the suppression of PRL or THs.